Pengelolaan Dana Desa dalam Pemberdayaan Masyarakat - Febby Febriantika Noer Fisabililah; azizatun rochamatul Nisaq; Siti Nurrahmawati (Universitas Muhammadiyah Mataram, 2020)
The purpose of this study is to describe the management of the Village Fund in empowering villagers and to find out the results of managing village fund allocations in community empowerment. The Village Fund Allocation Management Research in Community Empowerment was conducted at the Deket Kulon Village, the Deket District, Lamongan Regency. Village fund allocations are central and regional financial balance funds received by regencies / cities which are distributed in proportion to each village proportionally, at least 10% (ten percent). The allocation of village funds is intended for the administration of village government and community empowerment. This research uses a qualitative method with a descriptive approach. The results show that the results of village fund management can be used for environmental, economic and community empowerment. By emphasizing community participation as the key through the role of stakeholders so that the planned program can work effectively.